Analisis Laporan Keuangan Sebagai Pendukung Keputusan Pemberian Kredit Modal Kerja PT. Bank Maspion Tbk Cabang Surabaya - Rahayu, Pudji; Dewi Suprihandari, Miya (CV. Lafadz Jaya, 2022)
For banks, one of the main sources of income is the distribution of credit funds, including working capital loans. The distribution of funds with debtors is carried out under certain conditions by analyzing the financial statements of prospective debtors for a certain period. It was the goal of this investigation to find out whether or not the prospective debtor firm would perform well as a borrower of working capital. Preparation of research findings via the use of descriptive methodologies. Research shows that borrowers qualify for working capital loans, as evidenced by the findings.